Surface modification of hydroxyapatite nanoparticles - Ng, Shing Yeong. (2009)
This report presents a study of the surface modification of hydroxyapatite nanoparticles (HNPs) through the use of phosphonate functionalized dendrimers. Successful sysnthesis of the dendron substituted with phosphonate functional group enables attachment to the nanoparticles. The tags were characterized through nuclear magnetic resonance spectroscopy (NMR) before attachment to HNPs. Affinity of these phosphonate tags were tested and proven through analysis with Fourier-transformation infrared spectrometry (FTIR).